Differences in reactivity of paracoccidioidomycosis sera with gp43 isoforms - Souza, M. C.; Gesztesi, J. L.; Souza, A. R.; Moraes, J. Z.; Lopes, J. D.; Camargo, Z. P. (Blackwell Science, 1997)
The glycoprotein gp43 from Paracoccidioides brasiliensis is the main antigenic component in paracoccidioidomycosis (PCM) because it is recognized by 100% of PCM patients. It has also been shown that different fungal strains produce gp43 with at least four isoform profiles. In this study, different isoform profiles from gp43, with pIs ranging from 5.8 to 8.5, were affinity purified from various P. brasiliensis (B-339, S.S., 1925 and I-9) exoantigens. Because of the isoform heterogeneity, we questioned whether those isoform profiles could be similarly recognized by acute or chronic PCM patients. By using a specific and sensitive method for detection of human IgG anti-gp43 antibodies, the monoclonal antibody capture immunoassay, we report that not all gp43 isoform profiles are equally recognized in PCM sera when anti-gp43 MAb 17c was employed as capturing antibody. Our result showed that recognition of pI 8.5 gp43 isoform was significantly lower for both acute (56%) and chronic patients (71%), compared with gp43 isoforms from the standard strain B-339. on the other hand, when anti-gp43 MAb 8a, which recognizes a different antigenic epitope was used to capture the different gp43 isoform profiles, all patient's sera reacted similarly. The results described suggest that not all the antigenic epitopes expressed by gp43 are equally present in all P. brasiliensis strains.
Keywords: gp43 isoforms; P-brasiliensis; reactive sera